Multifunctional magnetoelectric sensing and bending actuator response of polymer-based hybrid materials with magnetic ionic liquids - Fernandes, Liliana C. (2023)
With the evolution of the digital society, the demand for miniaturized multifunctional devices has been increasing, particularly for sensors and actuators. These technological translators allow successful interaction between the physical and digital worlds. In particular, the development of smart materials with magnetoelectric (ME) properties, capable of wirelessly generating electrical signals in response to external magnetic fields, represents a suitable approach for the development of magnetic field sensors and actuators due to their ME coupling, flexibility, robustness and easy fabrication, compatible with additive manufacturing technologies. This work demonstrates the suitability of magnetoelectric (ME) responsive materials based on the magnetic ionic liquid (MIL) 1-butyl-3-methylimidazolium tetrachloroferrate ([Bmim][FeCl4]) and the polymer poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE) for magnetic sensing and actuation device development. The developed sensor works in the AC magnetic field and has frequency-dependent sensitivity. The materials show voltage responses in the mV range, suitable for the development of magnetic field sensors with a highest sensitivity (s) of 76 mV·Oe−1. The high ME response (maximum ME voltage coefficient of 15 V·cm−1·Oe−1) and magnetic bending actuation (2.1 mm) capability are explained by the magnetoionic (MI) interaction and the morphology of the composites.